Radical anions of acyclic vicinal oligoketones: an electron spin resonance study - Dörner, Thomas; Gleiter, Rolf; Neugebauer, Franz Alfred (Tetrahedron, 1999)
Radical anions of acyclic vicinal oligoketones with up to five CO units, 1a-d•- and 2a-c•-, were generated by reduction of the parent compounds with potassium in presence of kryptofix® 222 and studied by ESR measurements. The inverse correlation between g-values and the amount of spin populations on the terminal substituents prove that these radical anions are extended π-systems. Properties of the radical anions are reported.
Gesehen am 13.11.2020